'Vampires don't do dishes': Old myths, the modern world, horror and the mundane in What We Do in the Shadows (2014). Issue 2 (1st October 2018) - Wright, Andrea
The New Zealand horror-comedy What We Do in the Shadows (2014) emerged at a time when contemporary cinema had been showing a renewed and sustained interest in vampire fiction. Whilst it was not the first to offer a humorous reworking of vampire mythology, this parody is striking for it comes from a strong tradition in New Zealand cinema of disrupting genres, an approach that can be observed, for instance, in Peter Jackson's early work. What We Do in the Shadows creatively utilizes generic tropes and intertextual references whilst relocating supernatural creatures of the old world into a contemporary Wellington. As this article argues, the comic potential is opened up in the film by a particular convergence of the spectacular and the mundane. In this environment, blood-drinking and the practicing of the dark arts sit alongside everyday domestic tasks and cleaning rotas in a household of vampires. The film, it will be established, not only challenges and disrupts established horror genre conventions and expectations by repositioning them in a sitcom format, it also playfully engages with representations of masculinity and the homosocial in a house-share environment. In addition, by positioning the narrative in a New Zealand context, the film is able to localize the myths and stories of the old world and thus further destabilize recognized generic traditions.